Non-invasive diagnostic methods for fatal familial insomnia - Eryk Mikos; Sara Moqbil; Joanna Dmochowska; Martyna Wasyluk; Wanesa Góralczyk (Kazimierz Wielki University, 2022)
Fatal familial insomia (FFI) is a dominant autosomal genetic prion disease characterised by progressive sleep impairment, autonomic nervous system disorders and motor symptoms associated with significant loss of nerve cells in the medial thalamic nuclei. Making a diagnosis of FFI requires the presence of a certain or probable recognised first-degree relative of the patient, together with neuropsychiatric disorders present. In turn, the detection of the PrP mutation allows the diagnosis to be definitively established. In addition, three other tests - polysomnography, brain imaging and cerebrospinal fluid examination - can be helpful. Fatal familial insomnia is not a fully understood disease. Diagnosis is based on the presence of symptoms of the disease. An important step in diagnosis will be the development of non-invasive diagnostic tests that are reliable in the early and presymptomatic stages of the disease. Polysomnography, imaging studies (PET, SPECT) and cerebrospinal fluid examination should be improved and widely accepted.